A probabilistic epidemic forwarding method for resource-constrained heterogeneous delay tolerant internet of things. (11th September 2019) - Karimi, Shiva; Darmani, Yousef
Internet of things (IoT) is defined by networks of physical objects called smart things able to sense the environment, compute the results and communicate among themselves. IoT development needs to overcome many challenges regarding its constraints. Using IoT devices in delay tolerant networks (DTNs) scheme seems to be a solution to overcome its resource constraints and intermittent connectivity. Limited available battery and buffer size in small objects motivates the researchers to find optimised DTN routing schemes. DTNs are wireless networks that do not often have an end to end path between the source and destination objects. Epidemic routing (ER) protocol is a simple way to perform routing in such networks which is not effective from the energy point of view. To solve this problem the probabilistic epidemic (p-epidemic) routing protocol for the heterogeneous sets of smart objects is suggested. The accuracy of this forwarding method is supported by simulation results.